Through the Reactive to Proactive Thinking: Foresight of the AUKUS Agreement Rational Practice in the Indo-Pacific - Rizki Apriliana, Adhitya Nini (Faculty of Law, Universitas Jambi, 2024)
The AUKUS security pact between Australia, the UK, and the US, aimed at promoting prosperity in the Indo-Pacific has successfully generated significant attention. This alliance, rooted in the shared history of these powerful nations, includes the development of nuclear-powered submarines and enhanced underwater capabilities. The rise of China, particularly its actions in the South China Sea, has created tension in the region and presented a dilemma for ASEAN. The emergence of AUKUS has raised questions about its impact on ASEAN's role and whether the pact is intended to contain China. Some perceive AUKUS as a challenge to ASEAN centrality, potentially undermining the organization's ability to maintain stability and cooperation in the region. This research, using both legal and conceptual analysis, finds that AUKUS is not designed to directly confront China militarily. While AUKUS acknowledges the challenges posed by China's growing influence, it emphasizes a commitment to a free and open Indo-Pacific through cooperation rather than confrontation. This finding should reassure ASEAN and reduce concerns about the pact's destabilizing potential. Instead of viewing AUKUS with apprehension, ASEAN should explore ways to engage with the pact to address shared concerns and promote regional stability.